The effectiveness taping on functional performance : a systematic review / Muhammad Adib Fikri Lukman - Lukman, Muhammad Adib Fikri (2021)
Taping is one of the external elements that used to prevent re-injury and to ensure athlete able to return to sport early. Taping commonly used to prevent, protect, support, and strengthen the joint. The motion of weakened muscles of injured joint could be limited by taping to prevent excessive injury. The purpose of this review to provide an overview concerning the effectiveness of taping toward speed, agility, flexibility and stability on the sport performance abilities with consideration the mechanism of Kinesio Tape (KT). PubMed and Google scholar database were systematically searched which are studies divided into four group, speed, agility, flexibility, and balance. The inclusion criteria were applied are participant were identified as non-athlete and athlete, the study design compare the type of tape, the application method of KT, the outcomes were the sport performance or daily activity, and involve in randomization. Seventeen studies met the inclusion criteria. The functional performance included, 20-meter sprint, agility test, flexibility test, and star excursion balance test (SEBT). From seventeen studies, only five studies that revealed the significant result of the effectiveness taping toward the functional performance and the other studies result are not significant. Based on the result, there is not enough evidence to show that the mechanisms of taping that are effective for functional performance Further research is need to investigate the effectiveness of taping on functional performance using participant did not regularly do any exercise.